(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The paper analyses the various creative approaches involve in print advertisement which refers to adoption of certain advertising appeals used by the advertisers to attract the attention and interest of the consumers. This paper also encompasses the practices, review and analysis of different elements used in advertising in the form of special or fictitious characters, cartoons and caricatures, brand mascots, trademarks which represents and gratify the visual appeal of the product and communicate about the brand and its offering to the consumers in various occasions. In addition, the study also focuses on the association of cartoons, caricatures and other imaginative characters with children in Indian advertising. The study also focuses on the case study of advertising strategies of Vodafone India and Perfetti Van Melle India for better understanding of the relevance of joke in Indian advertising.